Covid 19: A Challenging Situation for the World - Mohit Gangwar, Brijesh Kumar Ojha, Himanshu Kumar Shukla, Aditya Pratap Singh, Rohit Srivastava, Sapna Singh (International Journal of Advanced Science and Technology, 2020)
When it comes to December 2019, an outbreak of a Novel Corona virus emerged within the community of Wuhan found Hubei province within Central China. The virus has formally been called as serious acute respiratory syndrome corona virus as well as the condition as corona virus illness 2019. On January 30, 2020, the World Health Organization (WHO) declared the outbreak like a public wellness critical of international problem. As on April 30, 2020, 3,220,182 laboratory confirmed cases, which includes 228,216 deaths, are reported from over 200 nations. This Novel Corona virus creating challenges around the world. Keywords: Asian, China, Corona Virus, Covid 19, Pandemic, Public Health, WHO, World Health Organization.